Effects of rapid weight loss in male and female wrestlers - Marten, A. D.; Mattin, M. D.; Rumps, M. V.; Saraf, S. M.; Mulcahey, M. K. (The Journal of Strength and Conditioning Research, 2025)
The long-standing practice of rapid weight loss (RWL) of wrestlers and other combat athletes is known as "cutting weight." This practice often consists of rapid dehydration and malnutrition to "weigh-in" at a lower weight class for competition. There are multiple negative nutritional and psychological implications in wrestlers because of cutting weight including significantly increased risk of athletic injury, decreased serum testosterone and increased serum cortisol, as well as an increased risk of eating disorders and hormone fluctuations in female athletes. In addition, literature suggests a decrease in athletic performance for athletes undergoing >5% RWL. The purpose of this narrative review was to provide an overview of the implications of weight cutting on athletic performance and overall well-being, and to highlight specific medical, physiological, and psychological effects in male and female wrestlers to aid healthcare workers in making recommendations regarding weight cutting practices.